O acesso à justiça sob o enfoque da teoria da justiça de John Rawls - Rios, Vinícius Custódio (2017)
The objective of this work is to study a model of justice that can be objectively appropriated by modern democratic society, addressing the application of justice by the judiciary, providing a reflection on the meaning of some terms such as justice, a sense of justice and equity. To do this study will be used the theory of justice developed by John Rawls. We will seek to identify the applicability of John Rawls' theory of justice in judicial decisions, characterizing and highlighting the relevance of equity so that there is an appropriate and fair mechanism in conflict resolution. The research methodology used to carry out this dissertation is the bibliographical one with doctrinal and jurisprudential grounds, under a deductive and in some points inductive approach